Penerapan Asas Keadilan dalam Tolok Ukur Keberhasilan Masa Percobaan Kerja - Jeance Tamimah; Saprudin Saprudin (Lembaga Yasin AlSys, 2026)
Provisions on probationary employment in employment relationships require fair, objective, and transparent assessment standards so as not to create legal uncertainty and harm workers. This study aims to analyze the application of the principle of justice in determining benchmarks for the success of probationary employment and to assess legal protection for workers based on Article 60 of Law Number 6 of 2023. This study used a normative legal method with statutory and conceptual approaches through a literature study of primary, secondary, and tertiary legal materials. The results showed that the regulation of probationary employment in statutory provisions has not provided clear, objective, and transparent benchmarks regarding workers’ success during the probationary period. This normative gap has the potential to create legal uncertainty and open opportunities for employers to abuse their authority through subjective assessments and the use of standard-form agreements that disadvantage workers. The application of the principle of justice, both procedurally and substantively, has also not been fully realized in practice. The conclusion of this study emphasizes the need for regulatory reform that explicitly governs fair, transparent, and measurable assessment standards for probationary employment, accompanied by evaluation mechanisms and adequate legal protection for workers. These findings contribute to strengthening labor law studies, particularly in promoting legal certainty and worker protection in PKWTT employment relationships.